The Influence of Online Learning Media on Students' Learning Outcomes: Survey in SMA 1 Cawang Baru Jakarta - Nadiah; Tsania Nabilah (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
When online learning media is used effectually, it improves students’ learning outcomes. Conversely, the results may not be beneficial if you do not use inappropriate online learning media that do not satisfy students' needs. The purpose of this study is to collect valid data on the learning outcomes of survey students at SMA 1 Cawang Baru Jakarta using online learning media. "Descriptive correlational analysis" was used to analyze the data. Using PTS results, the data was collected using cluster sampling by distributing a 20-item questionnaire for variable X (Online Learning Media) and variable Y (Student Learning Outcomes) (Mid Semester Assessment). Product Moment is used to analyze data. It yields "rxy" or "or" of 0.467, while "rt" is significant at 5% = 0.355 and 1% = 0.456. Thus, if ro>rt is significant at 5% or 1%, the Null Hypothesis (Hn) is rejected, whereas the Alternative Hypothesis (Ha) is accepted or approved. The Influence of Online Learning Media Against Student Learning Outcomes Survey at SMA 1 Cawang Baru Jakarta indicates sufficient correlation.